President's Message - Hollett, Sharon (Operating Room Nurses Association of Canada Journal, 2024)
ORNAC members started a significant conversation this fall when we successfully reached many of our members, through an online town hall format, and began a discussion about our membership categories. There is debate about our relationship with our perioperative nursing colleagues and around whether it is time for a change to ORNAC’s membership categories. Should Licensed/Registered Practical Nurses (LPNs/RPNs) be categorized as full members with voting privileges and the ability to serve on the Board of Directors? It has been a challenge to effectively chair these town hall meetings to ensure that all voices are heard but it is, however, proving to be rewarding work. This has resulted in a frank and open conversation that will determine how we move forward as an organization. I have, over the past year, heard from both Registered Nurses and Licensed/Registered Practical Nurses in my workplace and through my role with ORNAC on this subject. The views expressed to me on full membership status for LPNs/RPNs has been divided.